KINERJA PEGAWAI HONORER PADA DINAS PENDIDIKAN KABUPATEN JAYAWIJAYA - Irsan Yelipele (JI@P, 2018)
This research was intended to describe work performance of honoraryemployees at the Office of Education in Jaya Wijaya Regency. Workperformance was measured by using indicators of work performancequality, work performance quantity and timelines of work performance.This research also describes the inhibating as well as supporting factorsinfluencing upon work performance. This research manipulatedqualitative approach. Research result indicated that firstly, the quality ofwork of the honorary employees found to be effective, regardless oftheir degree of educational level and of geographical obstacles in whichthe roads have not been paved. Secondly, dealing with the quantityaspect, it was found that the amount of 50 honorary employees were notenought to run the job. In order to overcome this problem, the civilteachers collaborated sinergically with the honorary teachers.Meanwhile, so that the learning process in remote areas works well, thenumber of voluteer teachers were added. Thirdly, concerning thetimelines aspect, research result showed that especially in remote areasin which there is no paved road, teaching and learning process did notrun effectively.Key words: work performance; quality of work; quantity of work; timelines